1986
DOI: 10.1128/aem.51.1.101-104.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics of Edwardsiella ictaluri

Abstract: A total of 119 isolates of Edwardsiella ictaluri collected over the last 7 years from several states were biochemically characterized. Although not very reactive biochemically, this bacterium shows a high degree of homogeneity. Differences were found only in the production of gas from formate or from glucose at 37C and in the production of hydrogen sulfide as detected by lead acetate paper. Analysis of E. ictaluri by year or geographic area indicated that some differences existed, but no clear-cut biotypic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 5 publications
4
33
0
Order By: Relevance
“…There was no difference in the profile for the E. ictaluri challenge and recovered strains in this study. The Vietnamese E. ictaluri isolates appear to be slightly less biochemically reactive compared with USA strains (Waltman, Shotts & Hsu 1986). Nevertheless, all E. ictaluri isolates recovered from the affected P. hypophthalmus with clinical signs of BNP had similar identification profiles.…”
Section: Discussionmentioning
confidence: 85%
“…There was no difference in the profile for the E. ictaluri challenge and recovered strains in this study. The Vietnamese E. ictaluri isolates appear to be slightly less biochemically reactive compared with USA strains (Waltman, Shotts & Hsu 1986). Nevertheless, all E. ictaluri isolates recovered from the affected P. hypophthalmus with clinical signs of BNP had similar identification profiles.…”
Section: Discussionmentioning
confidence: 85%
“…Chondroitinase activity was proposed to be one virulence contributor in Edwardsiella spp. (Waltman, Shotts & Hsu 1986) and mediates the cartilage degradation in the chronic 'hole-in-the-head' lesion (Shotts & Cooper 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It was first isolated in 1976 from an epizootic in Alabama (Hawke 1979;Hawke et al 1981). Edwardsiella ictaluri is a serologically and biochemical homogeneous species (Hawke 1979;Hawke et al 1981;Waltman et al 1986;Lobb et al 1993), although one study analysing genetic footprints of several isolates found four subgroups (Bader et al 1998).…”
Section: Introductionmentioning
confidence: 99%